Reaching the Hard to Reach: Mobile Development Screening Van to the Rescue - Busillo-Aguayo, Joannie; Murawski, Wendy; Weiner, Ivor (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Currently more than 15% of children have an emotional, behavioral, or developmental concern. In spite of recommendations by the American Academy of Pediatrics and the Centers for Disease Control and Prevention to conduct universal developmental surveillance and screening with children at 9, 18, and 24 months of age, fewer than 30% of children under 6 years of age ever receive a developmental screening. Children in low-income and diverse communities are even less likely to be screened by a medical provider and/or referred for further diagnostic evaluation when predictive concerns are identified. As part of a cross-agency collaborative effort involving a family resource center, a child care resource and referral agency, a regional center for developmental disabilities, and a master's degree program in early childhood education, the Mobile Developmental Screening Van Project conducted outreach to provide free developmental screening with families of children 0-8 years of age in diverse and low-income communities within the greater Los Angeles County. Using the Parent Evaluation of Developmental Status (PEDS) screening tool, 94 children were screened over the course of 6 months, with 33% showing 2 or more predictive concerns that resulted in referrals for further diagnostic evaluation. The feasibility of reaching families in hard to reach communities using a mobile screening van, as well as study limitations and recommendations for next steps, are discussed.